Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals".
-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]
(2x - 3)(4x + 9)(2x + 3) = (2x - 3)(2x + 3)(4x + 9) = [(2x)^2 - (3^2)](4x + 9) = (4x^2 - 9)(4x + 9) = (4x^2)(4x) + (4x^2)(9) - (9)(4x) - (9)(9) = 16x^3 + 36 x^2 - 36x - 81
4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3
2x - 5 - 4x + 8= 2x - 4x - 5 + 8= -2x + 3
2x+17 = 4x-3 2x-4x = -3-17 -2x = -20 Answer: x =10
If that's - 4x, the answer is (2x + 3)(2x - 5) If that's + 4x, the answer is (2x - 3)(2x + 5)
-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]
(2x - 3)(4x + 9)(2x + 3) = (2x - 3)(2x + 3)(4x + 9) = [(2x)^2 - (3^2)](4x + 9) = (4x^2 - 9)(4x + 9) = (4x^2)(4x) + (4x^2)(9) - (9)(4x) - (9)(9) = 16x^3 + 36 x^2 - 36x - 81
4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3
2x - 5 - 4x + 8= 2x - 4x - 5 + 8= -2x + 3
2x+17 = 4x-3 2x-4x = -3-17 -2x = -20 Answer: x =10
4x - 7 = 2x + 15 4x = 2x +222x = 22x = 11
4x-1=2x+1
2x + 4x - x = 5x
8x-2x+4x=10x
8x2 + 2x - 1 = 8x2 + 4x - 2x - 1 = 4x(2x + 1) - 1(2x + 1) = (4x - 1)(2x + 1)
2x + 33 = 4x + 11 -11 -11 2x + 22 = 4x -2x -2x 22 = 4x Divide each side by 4 x = 5.5